The Relationship Between Student Perceptions In The Use Of Google Classroom Media In Pai Learning On Cognitive Learning Achievement - Nur'aliya, Hanny Rizqiyana (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The purpose of this study was to determine the relationship between students' perceptions of the use of Google Classroom in learning Islamic Religious Education (PAI) and their cognitive learning outcomes. A total of 78 students of grade XII of SMK Panca Bhakti Banjarnegara became the research subjects. This study used a quantitative approach. Data were collected through interviews, attitude scales, and documentation. Meanwhile, to test the hypothesis using simple linear regression analysis.Based on the research data, the majority of students, 67% of all respondents, scored well and thought that the use of Google Classroom materials in PAI learning was beneficial. Similarly, those who indicated that students' cognitive learning achievement in PAI learning was classified as good amounted to 58% of the total respondents who achieved a good score in the interpretation category. In addition, a strong positive correlation was seen between students' perceptions of the use of Google Classroom media in PAI learning and their cognitive learning achievement. Based on the significance value of 0.000 <0.05 and the coefficient of determination (R Square) of 0.449, this study revealed that the findings of this study explained 45% of the variability in cognitive learning achievement. This indicates that students' perceptions about the use of Google Classroom in PAI learning represent 45% of the variability in cognitive learning achievement.This finding suggests that students' perspectives on using learning media play an important role in their cognitive learning achievement. This positive relationship emphasizes the importance of evaluating and improving the utilization of Google Classroom media in the context of distance learning, especially in PAI subjects in vocational high schools. Thus, this study provides an important foundation for the development of efficient and effective distance learning strategies through online media such as Google Classroom.